2013
DOI: 10.1520/acem20120009
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Direct Shear Testing of Recycled Construction and Demolition Materials

Abstract: Laboratory large-scale direct shear tests were carried out on five different recycled construction and demolition materials, such as crushed concrete (CC), crushed rock (CR), crushed brick (CB), reclaimed asphalt pavement (RAP), and recycled glass (RG). The shear strength parameters were evaluated with a large shear test machine for different values of normal stress ranging from 30 to 200 kPa. Resulting values of cohesion were found to vary in a wide range between 8.55 kPa to 284.5 kPa, whereas coefficient of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…It is worth noting from Figure 2 that the CBR increased with decreasing RAP and increasing RCA content in the blends. This indicates that RCA is a higher quality recycled aggregate as compared to RAP, which is consistent to the findings of several authors (Arulrajah et al, 2013b, Piratheepan et al, 2013. This would furthermore justify why several road authorities internationally have specifications available for the usage of 100RCA in pavement subbases but not for 100RAP as well as the current requirement to stabilize RAP with cement or blending with other high quality aggregates (Taha et al, 2002, Puppala et al, 2012.…”
Section: Laboratory Experimentation Methodologysupporting
confidence: 83%
See 1 more Smart Citation
“…It is worth noting from Figure 2 that the CBR increased with decreasing RAP and increasing RCA content in the blends. This indicates that RCA is a higher quality recycled aggregate as compared to RAP, which is consistent to the findings of several authors (Arulrajah et al, 2013b, Piratheepan et al, 2013. This would furthermore justify why several road authorities internationally have specifications available for the usage of 100RCA in pavement subbases but not for 100RAP as well as the current requirement to stabilize RAP with cement or blending with other high quality aggregates (Taha et al, 2002, Puppala et al, 2012.…”
Section: Laboratory Experimentation Methodologysupporting
confidence: 83%
“…In recent years, efforts have been made to incorporate RAP into pavement base or subbase applications (e.g. Maher and Jr., 1997, Taha et al, 2002, Park, 2003, Taha, 2003, Blankenagel and Guthrie, 2006, Poon and Chan, 2006, Cho et al, 2011, Piratheepan et al, 2013. RAP stabilized with cement binders has been reported to perform satisfactorily in pavement base and subbase layers (Hoyos et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used various methodologies, such as direct shear tests, to evaluate the shear strength and resistance of a wide range of materials, from recycled construction and demolition materials to stabilized earth and polymeric substances. Two papers have specifically focused on the shear strength properties of recycled materials and geogrid-reinforced demolition waste [145,146]. Another paper explored shear testing for polymeric materials [147].…”
Section: Shear Strength Testing: Evaluates the Material's Ability To ...mentioning
confidence: 99%
“…To use a modified large-scale direct shear LSD apparatus, the interface shear strength characteristics of the aggregate of interfaces in geogrid-reinforced building and demolition were studied [7]. Various types of materials testing and other recent direct or interface shear test research studies can be found in the literature [8][9][10][11]. Based on the abovementioned gaps, additional research is needed on the interfacing parameters between road-base materials and geosynthetics for road-base reinforcement and subgrade stabilization.…”
Section: Introductionmentioning
confidence: 99%